Application of Triangulation and IPA for Identifying Tourism Service Aspects Problems in Selorejo Dam - Maulidah, Rayhan; Wicaksono, Agus Dwi; Wijayanti, Wawargita Permata; Maineh, Ndongkeh Nelson (Perencanaan Wilayah dan Kota FT UB, 2024)
Selorejo Dam Tourist Park is a natural and artificial tourist attraction in Malang Regency. The existence of this tourism has a direct influence on the economy of the surrounding community. Based on Malang Regent Regulation Number 11 of 2022 concerning the 2023 Regional Government Work Plan, Selorejo Dam Tourism Park is one of the leading tourist attractions in Malang Regency that can be developed. This tourism has great potential to be developed, but the number of tourists is decreasing yearly. This can occur due to problems with aspects of tourism service. Tourism service is a minimum requirement for the development of a tourist destination. The tourism service aspect consists of 6A: Attraction, Accessibility, Amenities, Ancillary Services, Activities, and Available Packages. This research aims to identify problems with the service aspects of the Selorejo Dam Tourist Park. The analytical method used is triangulation analysis, which consists of observation, questionnaires (Importance-Performance Analysis (IPA)), and interviews. Triangulation analysis aims to reduce bias as much as possible at the data collection and analysis stage. Meanwhile, IPA determines tourists' interests and satisfaction with aspects of tourism services. The research results show that the problems with tourism service aspects resulting from each data collection differ. The issues of each data collection are compared and then concluded. In conclusion, 20 Selorejo Dam Tourist Park service elements have problems. The results of this study are expected to be a reference for the managers of Selorejo Dam Tourist Park to develop the aspects of tourism services.